Prevalensi Keluhan Kesehatan pada Pekerja Industri Percetakan - Moch. Sahri; Fain Roudlotull Jannah; Alfina Novita Dewi; Daffa Ade Azmi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Printing is an industry that is rarely paid attention to, especially in terms of its occupational safety and health. Of course this is very unfortunate considering the level of hazard risk to the printing industry workers is very complex. The risk of danger to the printing industry itself can be seen from the various types of raw materials used, the activities and body postures of workers while doing their work. This study aims to determine health complaints due to chemical exposure experienced by printing industry workers. This type of research is an observational study. The data collection method is done by using a health complaint questionnaire. The sample in this study were 24 printing industry workers. The data analyst used was descriptive analysis. The results showed that the frequency of health complaints experienced by workers in the printing industry were coughing, sneezing, phlegm, shortness of breath, nausea, dizziness, fatigue, shoulder pain, low back pain, back pain, neck and arm pain.